Effect of reaction temperature on the protein structure and the ability to encapsulate β‐carotene of WPI‐dextran conjugates. Issue 6 (25th May 2020) - Xi, Chunyu; Kang, Naixin; Zhao, Changhui; Song, Hongxin; Liu, Yujia; Zhang, Tiehua
Abstract : Abstract: In this paper, we studied the effect of glycosylation reaction on the molecular structure and functional properties of whey protein isolate (WPI), and studied the effect of reaction temperature (50 to 90 °C) on the molecular structure and functional properties of WPI–dextran conjugates (WPI‐D). The results of the extent of glycation (EG) and sodium dodecyl sulfate–polyacrylamide gel electrophoresis confirmed the formation of WPI‐D. Circular dichroism (CD), Fourier transform infrared spectrum, and fluorescence spectroscopy indicated that the molecular structure of WPI was changed after glycosylation—the β‐sheet content was decreased and the tryptophan content was increased. The emulsifying properties and the ability to encapsulate β‐carotene of WPI‐D were improved compared with WPI ( P < 0.05). When the reaction temperature was 70 and 80 °C, the EG and the ability to encapsulate β‐carotene of WPI‐D were better ( P < 0.05), which was related to protein unfolding. However, due to the polymerization between the WPI molecules, the emulsion activity index of WPI‐D and the ability to encapsulate β‐carotene were lowered at 90 °C ( P < 0.05). Therefore, the glycosylation reaction can change the molecular structure and functional properties of WPI; the emulsifying properties and the ability to encapsulate β‐carotene of WPI‐D can be changed by controlling the reaction temperature of glycosylation. Practical Application: The glycosylation reaction can change the molecular structure and functional properties of Whey protein isolate; the emulsifying properties and the ability to encapsulate β‐carotene of WPI‐dextran conjugates can be changed by controlling the reaction temperature of glycosylation.